2014
DOI: 10.1016/j.yexcr.2014.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Identification and expression analysis of the zebrafish orthologues of the mammalian MAP1LC3 gene family

Abstract: Elsevier's AAM Policy: Authors retain the right to use the accepted author manuscript for personal use, internal institutional use and for permitted scholarly posting provided that these are not for purposes of commercial use or systematic distribution. Permitted scholarly postingVoluntary posting by an author on open websites operated by the author or the author's institution for scholarly purposes, as determined by the author, or (in connection with preprints) on preprint servers. 7th October, 2014Identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…At 2 days post fertilization (dpf), abundant GFP-LC3 puncta are present in the trunk region of the morphant compared with the control embryos (Fig. 2a–d) and this difference is even more pronounced after chloroquine treatment, known to block autophagosome degradation in zebrafish3435. On injection of in vitro -transcribed-capped human Hs1bp3 mRNA alongside the Hs1bp3 morpholino, we observe a partial rescue of the phenotype at 2 dpf both with and without chloroquine treatment (Fig.…”
Section: Resultsmentioning
confidence: 81%
“…At 2 days post fertilization (dpf), abundant GFP-LC3 puncta are present in the trunk region of the morphant compared with the control embryos (Fig. 2a–d) and this difference is even more pronounced after chloroquine treatment, known to block autophagosome degradation in zebrafish3435. On injection of in vitro -transcribed-capped human Hs1bp3 mRNA alongside the Hs1bp3 morpholino, we observe a partial rescue of the phenotype at 2 dpf both with and without chloroquine treatment (Fig.…”
Section: Resultsmentioning
confidence: 81%
“…In vivo studies indicate that rapamycin results in developmental delay in different organisms including Drosophila melanogaster, zebrafish and mice (6,13,14). Previous studies using zebrafish have identified significant effects of rapamycin on autophagy (15), prevention of hepatic steatosis (16), heart development (17) and demonstrated the importance of zebrafish as a mitochondrial and ribosomal disease model (18,19). Although the zebrafish is an emerging model in drug-screening and in vivo disease models (20), evolutionarily conserved effects of rapamycin on the zebrafish transcriptome in addition to the dose-dependency in embryonic/larval size and pigmentation have not previously been studied.…”
Section: Introductionmentioning
confidence: 99%
“…48 and 52 hpf-old embryos were firstly dechorionated and deyolked and then placed in sample buffer (2% sodium dodecyl sulphate (SDS), 5% β-mercaptoethanol, 25% v/v glycerol, 0.0625 M Tris–HCl [pH 6.8], and bromophenol blue) (16), heated immediately to 95°C for 10 min and then sonicated (Diagenode Bioruptor UCD-200) in an ice-water bath at high power mode for 10 min before loading onto polyacrylamide gels for electrophoresis (see below). The 96 hpf-old larvae were not deyolked before lysis in sample buffer.…”
Section: Methodsmentioning
confidence: 99%